Detection of Tuberculosis in Toddlers and its Risk Factor at East Perak Health Center Surabaya - Alifa Salsabila Azzahrain; Anisa Nur Afifah; Laura Navika Yamani (Universitas Airlangga, 2023)
Introduction: Tuberculosis is a contagious disease that can grow fast due to its transmissibility through aerosols. One of the countries with the highest tuberculosis rates is Indonesia with a case fatality rate of 11.59%. This study's objective was to examine the relationship between the physical condition of the house and the immune system and the incidence of tuberculosis in toddlers in Surabaya. Methods: This study used an analytic survey research design with a case control research methodology. The case population consisted of pediatric patients aged 0-5 years who were clinically diagnosed with pulmonary tuberculosis. The Chi-Square test was used to analyze bivariate data with a confidence level of 0.05 (α = 5%). Results and Discussion: The physical condition of the house that influenced the incidence of tuberculosis in toddlers were room temperature (p = 0.009; OR = 8.300; CI = 1.480-46.936) and room humidity (p = 0.000; OR = 7.600; CI = 1.609-35.906) while the immune system that affected the incidence of tuberculosis in toddlers were history of tuberculosis sufferers in the family (p = 0.018; OR = 6.000; CI = 1.266-28.498) and exclusive breastfeeding (p = 0.003; OR = 10.000; CI = 1.998-50.042). Conclusion: Houses with inadequate room temperature and humidity have an increased risk of tuberculosis development. Moreover, tuberculosis risk factors include a history of exclusive breastfeeding and a family history of tuberculosis. Health promotion by community health centers is expected to increase awareness of pediatric tuberculosis.